Cassava pullulanase and its synergistic debranching action with isoamylase 3 in starch catabolism - Wangpaiboon, Karan; Charoenwongpaiboon, Thanapon; Klaewkla, Methus; Field, Robert A.; Panpetch, Pawinee (Frontiers in Plant Science, 2023)
Pullulanase (EC 3.2.1.41, PUL), a debranching enzyme belonging to glycoside hydrolase family 13 subfamily 13, catalyses the cleavage of α-1,6 linkages of pullulan and β-limit dextrin. The present work studied PUL from cassava Manihot esculenta Crantz (MePUL) tubers, an important economic crop. The Mepul gene was successfully cloned and expressed in E. coli and rMePUL was biochemically characterised. MePUL was present as monomer and homodimer, as judged by apparent mass of ~ 84 - 197 kDa by gel permeation chromatography analysis. Optimal pH and temperature were at pH 6.0 and 50 ℃, and enzyme activity was enhanced by the addition of Ca2+ ions. Pullulan is the most favourable substrate for rMePUL, followed by β-limit dextrin. Additionally, maltooligosaccharides were potential allosteric modulators of rMePUL. Interestingly, short-chain maltooligosaccharides (DP 2 - 4) were significantly revealed at a higher level when rMePUL was mixed with cassava isoamylase 3 (rMeISA3),compared to that of each single enzyme reaction that required a much longer time of incubation. This suggests that MePUL and MeISA3 debranch β-limit dextrin in a synergistic manner, which represents a major starch catabolising process in dicots. Additionally, subcellular localisation suggested the involvement of MePUL in starch catabolism, which normally takes place in plastids.